Early Spinal Cord Pseudoatrophy in Multiple Sclerosis and their Treatment Through Interferon Beta - Waqas Ahmed, Sana Fatima, Momina Saleem, Husnian Hashim, Sana Farooq, Khushboo Chandio (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Multiple sclerosis (MS) frequently affects spinal cord (SC), resulting in motor, sensory, and autonomic impairment. Many pathological problems, including demyelination and neuroaxonal loss, are examined in vivo with MRI in MS. Objectives: This research was performed for confirming effects of early SC pseudoatrophy (PA) in MS treated using interferon beta on SC in early IFN therapy. Methods: PA was diagnosed using MRI and patients were classified based on McDonald’s 2010 criteria into 05 categories of clinical attacks. They were treated using IFN-1a 44 g, beginning after FCDE, administered thrice or once weekly for 2 years and their EDSS scores were baseline evaluated. Results: Kurtzke EDSS scoring system was implied to determine the disability of MS. After treating for 02 years, the Group A patients was scored 1.0 and Group B 1.5. The MS disability in SC was significantly reduced in both treatment groups, though, significantly enhanced domino effects (p<0.05) were observed in treatment group A administered with three doses weekly (51.41%) followed by single weekly (48.51%); and EDSS scores were significantly declined (p<0.05) from 2.5 to 1.0 and 1.5 respectively. Conclusion: It was evidenced that PA affected the SC and caused significant spinal lesions. PA of SC was utilized as biomarker to monitor therapeutic impacts in MS. The PA in MS-affected individuals was significantly treated in early arena and disability of MS of SC was significantly declined with interferons. Keywords: Interferons; McDonald’s scoring; Pseudoatrophy; Sclerosis.